2009
DOI: 10.1097/gim.0b013e3181afd322
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of population-based BRCA1/2 testing and ovarian cancer prevention for Ashkenazi Jews: A call for dialogue

Abstract: Purpose: About half of unaffected BRCA1/2 carriers have a negative family history, confounding efforts toward presymptomatic carrier identification. Ovarian cancer is preventable for known carriers but is otherwise highly lethal. Cost-effectiveness and gains in life expectancy are important factors in evaluating the desirability of population-based genetic screening, currently the only viable strategy to identify carriers with unrevealing family histories. Methods: Cost-utility analysis for a population-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 64 publications
0
66
0
5
Order By: Relevance
“…16,17 Ancestry-informed testing of a few common BRCA1/2 mutations has been proposed as a cost-effective approach in a number of populations including Ashkenazi Jews. [18][19][20][21][22][23][24][25] Diagnosing BRCA mutations triggers preventive measures in relatives, which contributes to the value of such screening approaches. 21 The identification of a prevalent founder mutation in a very specific part of the Tyrol may facilitate a long-term study to examine the true sensitivity, usefulness, and cost-effectiveness of routine testing of breast or ovarian cancer patients without any selection based on established HBOC criteria.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Ancestry-informed testing of a few common BRCA1/2 mutations has been proposed as a cost-effective approach in a number of populations including Ashkenazi Jews. [18][19][20][21][22][23][24][25] Diagnosing BRCA mutations triggers preventive measures in relatives, which contributes to the value of such screening approaches. 21 The identification of a prevalent founder mutation in a very specific part of the Tyrol may facilitate a long-term study to examine the true sensitivity, usefulness, and cost-effectiveness of routine testing of breast or ovarian cancer patients without any selection based on established HBOC criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Rubinstein et al 22 demonstrated that population BRCA genetic screening of women of the Ashkenazi Jewish population in the United States between the ages of 35 and 55 years would be cost-effective with regard to surgical prevention and treatment of ovarian cancer. Metcalfe et al 23 reported a significant response to a newspaper advertisement offering general BRCA genetic testing to Jewish women in Ontario, Canada.…”
Section: Genetics In Medicine | Volume 14 | Number 7 | July 2012mentioning
confidence: 99%
“…In 2005, the US Preventive Services Task Force recommended BRCA1/BRCA2 testing only for women with an increased-risk family history, defined in Ashkenazi Jews as any first-degree relative (or two second-degree relatives on the same side of the family) with breast or ovarian cancer. 5 As noted by Rubinstein et al, 1 subsequent studies have shown that approximately half of BRCA1/BRCA2 carriers identified after diagnosis of breast cancer and one third of carriers identified after diagnosis of ovarian cancer do not have significant family history of either cancer.…”
mentioning
confidence: 96%
“…As discussed by Rubinstein et al, 1 we have yet to determine the most effective pretest and post-test processes. Pretesting traditional genetic counseling should be compared with other methods, which may be less costly.…”
mentioning
confidence: 99%
See 1 more Smart Citation